Natural Ecosystem Surrounding a Conventional Banana Crop Improves Plant Health and Fruit Quality - Castelan, Florence P.; Castro-Alves, Victor C.; Saraiva, Lorenzo A.; Nascimento, Talita P.; Cálhau, Maria F. N. S.; Dias, Carlos T. S.; Cordenunsi-Lysenko, Beatriz R. (Frontiers in Plant Science, 2018)
Natural ecosystems nearby agricultural landscapes may provide rich environments for growing crops. Although biodiversity plays a crucial role in the functioning of agroecosystems, the effects of biodiversity on crop health and fruit quality are not well-understood. This study thus explores the effects of natural ecosystems surrounding a conventional banana crop on fruit quality and postharvest behavior, and aspects of crop health. The strategy is based on comparisons between two areas of conventional banana crops with identical planting time and cultural practices. The only difference between the areas is that one was surrounded by an Atlantic Forest fragment, while the other was inserted at the center of a conventional banana crop. Results show fruits with marked differences in their postharvest behaviors, including carbohydrate and hormone profiles, greenlife and, therefore, overall fruit quality. Interestingly, fruits harvested from plants nearby natural biodiversity showed higher greenlife and a more homogeneous profile than fruits harvested on the area surrounded exclusively by banana crops. Moreover, plants cultivated nearby natural biodiversity showed a lower severity index of black Sigatoka and higher levels of phenolic compounds, thus highlighting biodiversity management as a promising tool for improving crop health and quality.